2015
DOI: 10.2174/1566524015666150630125024
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Admission of an In Vitro Reconstructed Complexes of Human Recombinant Heat Shock Proteins and Melanoma Antigenic Peptides Activates Anti-Melanoma Responses in Mice

Abstract: Tumor-derived autologous antigenic peptides when bound to endogenous 70 kDa family heat shock proteins (HSP70) are able to induce effective T-cell responses against tumors. However, efficacy of HSPbased vaccines in clinical practical stand point still has a number of certain limitations including an activation of immune responses against alien non-human HSPs. In this study we reconstructed the complexes of human recombinant HSPs70 (human recombinant HSP70A1B and HSC70 mixture; hrHSPs70) with antigenic lowweigh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Therefore, a number of strategies utilizing HSPs to target the SRs of DCs have been developed [158]. Different studies reported different variants of HSP-based vaccines designed to target SRs, which included the harvesting of autologous HSP-TAA complexes [159], in vitro constructed HSP-TSA complexes [160,161] and fusions of HSPs to cancer peptides [162]. Eventually, all of these methods aim to develop a DC-targeting vaccine that will activate DCs in vivo after its administration to the patient.…”
Section: Scavenger Receptor Targetingmentioning
confidence: 99%
“…Therefore, a number of strategies utilizing HSPs to target the SRs of DCs have been developed [158]. Different studies reported different variants of HSP-based vaccines designed to target SRs, which included the harvesting of autologous HSP-TAA complexes [159], in vitro constructed HSP-TSA complexes [160,161] and fusions of HSPs to cancer peptides [162]. Eventually, all of these methods aim to develop a DC-targeting vaccine that will activate DCs in vivo after its administration to the patient.…”
Section: Scavenger Receptor Targetingmentioning
confidence: 99%
“…Expression vectors encoding Triticain-α variants were based on commercially available plasmids pET15b, pET26b(+), pET28a(+), pET30a(+), pET42a(+) (Merck Millipore, Billerica, MA, USA), pQE80L (Qiagen, Hilden, Germany), and pGEX-5X-1 (GE Healthcare Life Sciences, Pittsburgh, PA). Expression vector pQE80-6HIS-HSP70A1B as well as plasmids pET42-6HIS-Triticain-α, pQE80-6HIS-Triticain-α-GM, and pQE80-6HIS-Triticain-α-GM C154A were obtained previously [ 11 , 31 ]. Molecular cloning was performed according to the standard protocols [ 32 ].…”
Section: Methodsmentioning
confidence: 99%